Perceived parental behaviours and motivational processes among adolescent athletes in intensive training centres. A profile approach - Lienhart, N.; Nicaise, V.; Martinent, G.; Guillet-Descas, E. (Psychology of Sport and Exercise, 2020)
Parental behaviours influence athletes` psychological functioning in different ways. To date, research has typically explored parental behaviours one by one, and few papers have simultaneously considered sets of parental behaviours. The objectives of this study were to: (a) identify parental behaviours using a person-centred approach and differentiating mother`s and father`s behaviours; (b) explore the changes of parental behaviour profiles across the season; and (c) examine the prospective impact of parental behaviour profiles at the beginning of the season on athlete scores of motivation, satisfaction, and frustration of basic psychological needs at the end of the season. A longitudinal two-wave measurement design (beginning and end of a season) was used in the study. A sample of 226 French athletes completed self-reported questionnaires: (a) at the beginning and end of the season to measure the behaviours of their parents; and (b) at the end of the season to assess their motivation, satisfaction, and frustration of basic psychological needs. Latent profile transition analysis revealed three parental behaviour profiles: (a) moderate parental involvement; (b) moderate to high parental involvement; and (c) moderate mother`s involvement and low father`s involvement. The profiles were based on associated patterns of four mother`s and father`s behaviours: (a) directive behaviours; (b) active involvement; (c) praise and understanding; and (d) pressure. The three parental behaviour profiles remained stable across the season (i.e., inter- and intra-individual stability). Athletes who reported the moderate parental involvement profile at the beginning of the season had lower scores of controlled motivation and frustration of autonomy as well as higher scores of satisfaction of competence and relatedness at the end of the season than their counterparts from the two other profiles. This study contributes to enriching the complex picture of parental involvement in the sport to help sport organisations identify parents at risk of impeding their child`s development.